Breast lumps a guide to diseases of the breast - Smith, Jane, 1954-; Smith, Jane, 1954- (Tfm Pub., 2003)
This new edition of Breast Lumps (which was first published in 1994) provides updated information on both benign breast conditions and breast cancer. The book has been substantially revised, particularly with regard to the changes that have occurred in the treatment of breast cancer during the last few years. It discusses all aspects of the management of breast lumps and the ways in which this differs in the UK and USA.